VARIABEL ANTESEDEN INTENTION TO STAY PEKERJA MILENIAL DENGAN KERJA REMOTE DI JAKARTA SEKITARNYA - Kevin Kristiawan Elison; Sylvia Diana Purba (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The millennial generation that dominates the workforce today has dynamic characteristics and high turnover intention. Job design that is autonomous and passion is considered to make millennial more sustainable in one company. This study was conducted to examine the antecedent effect of the intention to stay variable, namely task characteristics autonomy, passion, and job satisfaction with the intention to stay with 100 millennial remote workers in Jakarta as respondents. Data obtained from questionnaires distributed via g-form with purposive sampling method and convenience sampling technique. Data processing using SMART PLS 3.0 software with Bootstrapping analysis method. The results of this study prove that job satisfaction can increase intention to stay and is able to mediate the effect of passion and task characteristics autonomy on intention to stay. The results also prove that passion can significantly increase job satisfaction and intention to stay. Likewise, job characteristic autonomy has a significant effect on job satisfaction. Passion, job characteristic autonomy, job satisfaction are antecedents of variables that determine the intention to stay for millennial workers with remote work. Keywords: intention to stay, job satisfaction, task characteristic autonomy, passion, remote workers